Analisis Kesulitan Peserta Didik Dalam Mengubah Pecahan Biasa Berdasarkan Gaya Kognitif Konseptual Tempo - Mulyawati, Ima; Lutfia, Puti Cahya (FKIP Universitas Mataram, 2025)
This study aims to identify the difficulties faced by fourth grade students in sorting ordinary fractions based on conceptual tempo cognitive style, and also reveal the factors that can influence it. The approach used is descriptive qualitative with a focus on the individual characteristics of learners. Data obtained through interviews with classroom teachers and giving practice tests on fractions designed in accordance with the indicators of reflective and impulsive cognitive styles. The results showed that students with reflective cognitive style are more likely to work on problems carefully and meticulously, but require a longer time. Conversely, learners with impulsive style can solve problems quickly but often make mistakes due to lack of accuracy. These findings indicate that the application of learning strategies that are tailored to the conceptual cognitive style of tempo can improve students' understanding and ability in fraction material. Therefore, it is important for teachers to consider students' cognitive style in designing an effective and adaptive learning style approach.